Development of Dusun Traditional Fermented Fish (Bosou Ikan) Using Different Concentrations of Tuhau (Etlingera coccinea) (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
This study aimed to determine the best formulation of Dusun traditional fermented fish (Bosou ikan) through sensory evaluation employing a 9-point hedonic test. Various concentrations of Etlingera coccinea, ranging from 0% to 8% w/w, were incorporated into fermented fish samples. Results revealed that the formulation containing 2% E. coccinea (F1) consistently exhibited superior sensory attributes, maintaining the traditional appearance while enhancing aroma, taste, and overall acceptability. Statistical analysis using the Friedman test confirmed F1's superiority, showing the lowest mean rank among alternatives (p
Keywords: Dusun; Traditional fermented fish; Bosou ikan; Tuhau; Etlingera coccinea